APPLICATION OF INTERACTIVE METHODS IN THE PROCESS OF TEACHING THE SUBJECT "MACHINE DETAILS" - Mustapakulov Sadik Ungiboyevich; Karimov Abror Kayumovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. We will begin the description of this article with a narration that was told a long time ago.